Feeding Style for Children Aged 0-59 Months of Buginese Ethnicity - Rudy Hartono1,4, Agustian Ipa1,4, Sirajuddin1,3,4, Aswita Amir1,4, Sharifah Intan Zainun Sharif Isha (Indian Journal of Forensic Medicine & Toxicology, 2020)
Background. The study of Feeding Style of children in ethnic Buginese was focused on caregiver styles to feeding practices that influences nutritional stunting. The purpose of this study was to determine feeding style of Bugis ethnicity. Method. The cross sectional study and the sample size is 300 subjects, selected by random sampling. Located in in Makassar City, South Sulawesi Provice Indonesia (starting January-December 2019). Enumerators in this study were students of the Applied Nutrition & Dietetic in Nutrition Department of the Health Polytechnic Makassar. Research ethics was obtained at the Makassar Health Polytechnic Ethics Commission. The results showed that stunting prevalence for children in Bugineses ethnicity was 22,7% and Feeding Style consists of four groups namely caring ( indulgent ), compromise ( authoritative ), free ( uninvolved ) and completely regulating ( authoritarian ). The conclusion is that the style of Bugis ethnic child feeding style consists of four groups namely indulgent, authoritative, uninvolved, and authoritarian.